Performance Prediction In Educational Data Mining using Neural Network - Mundhe, Shankar G; Gaikwad, Shital Y (International Journal of Computer Sciences and Engineering, 2019)
Educational system is facing the challenges to improve the quality of education and to make managerial decisions to achieve the quality. Student’s academic performance is the reflection of previous academic background. Performance prediction helps educational institute to support decision making procedures and to formulate better management plans. This performance record is important for the educational institution because they can learn from this to improve their quality by knowing the performance of the student. Educational data mining analyze these data and extract information from it. We can determine the status of student’s academic performance. For achieving this we can use techniques like decision tree, classification, data clustering and neural network and so on. In this paper, we will predict student’s semester wise performance.